Synthesis, Molecular Docking, Molecular Dynamic Simulation Studies, and Antitubercular Activity Evaluation of Substituted Benzimidazole Derivatives - Shankar Thapa; Mahalakshmi Suresha Biradar; Shachindra L. Nargund; Iqrar Ahmad; Mohit Agrawal; Harun Patel; Ashish Lamsal (Advances in Pharmacological and Pharmaceutical Sciences)
Tuberculosis, also known as TB, is a widespread bacterial infection that remains a significant global health issue. This study focuses on conducting a thorough investigation into the synthesis, evaluation of anti-Tb activity, molecular docking, and molecular dynamic simulation of substituted benzimidazole derivatives. A series of twelve substituted benzimidazole derivatives (1–12) were successfully synthesized, employing a scaffold consisting of electron-withdrawing and electron-donating groups. The newly synthesized compounds were defined by their FTIR, 1H NMR, and mass spectra. The microplate Alamar blue assay (MABA) was used to evaluate the antimycobacterial activity of the synthesized compound against Mycobacterium tuberculosis (Mtb). Compounds 7 (MIC = 0.8 g/mL) and 8 (MIC = 0.8 g/mL) demonstrated exceptional potential to inhibit M. tuberculosis compared to the standard drug (isoniazid). In addition, the synthesized compounds were docked with the Mtb KasA protein (PDB ID: 6P9K), and the results of molecular docking and molecular dynamic simulation confirmed the experimental results, as compounds 7 and 8 exhibited the highest binding energy of −7.36 and −7.17 kcal/mol, respectively. The simulation results such as the RMSD value, RMSF value, radius of gyration, and hydrogen bond analysis illustrated the optimum potential of compounds 7 and 8 to inhibit the M. tuberculosis strain. Hydrogen bond analysis suggested that compound 7 has greater stability and affinity towards the KasA protein compared to compound 8. Moreover, both compounds (7 and 8) were safe for acute inhalation and cutaneous sensitization. These two compounds have the potential to be potent M. tuberculosis​ inhibitors.